Strengthening Care for the Injured : Success Stories and Lessons Learned from Around the World. - Mock, Charles; World Health Organization. Violence and Injury Prevention (Geneva : World Health Organization, 2010)
"Injury accounts for a significant proportion of the world's burden of disease. Each year 5.8 million people die from injury and millions more are disabled. The response to this global health problem needs to include a range of activities, from better surveillance to more in-depth research, and primary prevention. Also needed are efforts to strengthen care of the injured. The World Health Organization (WHO) has responded to this need with a variety of actions. It has supported countries in setting up trauma care programmes and in developing their capacity to care for the injured. It has also developed, in consultation with global experts, guidelines to assist with the organization and planning of trauma care, such as Prehospital trauma care systems, Guidelines for essential trauma care, and Guidelines for trauma quality improvement programmes. These publications have been used in many countries and have helped to stimulate 'on the ground' improvements and policy changes. Efforts to improve care of the injured globally received a major boost in 2007 when the World Health Assembly (WHA) adopted resolution WHA60.22 on trauma and emergency care services. This called upon governments and WHO to increase their efforts to improve care for victims of injury and other medical emergencies. It also called upon WHO to raise awareness about affordable ways in which trauma and emergency care services can be strengthened, especially through universally applicable means such as improvements in organization and planning. Similarly, resolution WHA58.23 on disability, including prevention, management, and rehabilitation, requested WHO to provide support to countries in developing rehabilitation services for people with disabilities. In response to these requests WHO collected this set of case studies, documenting success stories and lessons learned from several countries. Through this publication, WHO seeks to increase communication and the exchange of ideas among those working in the field of trauma care, whether in the prehospital setting, in acute care in hospitals, or in longer term rehabilitation; to increase communication among those involved in planning, administering, advocating for, or directly providing trauma care services; and to increase communication among those working in the field of trauma care in different countries worldwide." - p. iii
Executive summary -- Introduction -- 1. Prehospital care -- 2. Hospital-based care -- 3. Rehabilitation -- 4. System-wide improvements -- Summary and lessons learned
Editors: Charles Mock, Catherine Juillard, Manjul Joshipura, Jacques Goosen.
Includes bibliographical references.
Keywords: Emergency medical services; Rehabilitation; Traumatology; Emergency Medical Services -- Case Reports; Emergency Medical Services -- organization & administration; Emergency Treatment -- Case Reports; Rehabilitation -- Case Reports; Traumatology -- Case Reports; Wounds and Injuries -- rehabilitation